Business service composability on the basis of trust - Hammadi, Adil; Dillon, Tharam S.; Chang, Elizabeth (IEEE, 2009)
In the real world a service in a business is usually composed of many component services. These component ser-vices join together to form a composite of components. The trustworthiness of component services determines the trustwor-thiness of this composite. This trustworthiness of composite ser-vice has a larger impact on the successful delivery of a service. In this paper we study that how we can determine the trustwor-thiness of this composite. Since the components in the composite form parallel or series and/or combination of parallel/series ar-rangements we use probability theory to determine the trustwor-thiness of composite service. We use a case study to demonstrate the concepts clearly.